2013
DOI: 10.1159/000350513
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight in Children Born to Mothers with Hyperthyroidism and High Birth Weight in Hypothyroidism, whereas Preterm Birth Is Common in Both Conditions: A Danish National Hospital Register Study

Abstract: ated with increased risk of preterm birth. Moreover, birth weight in children born to mothers with a diagnosis of hyperthyroidism was lower (adjusted difference -51 g, 95% CI -58 to -43 g) and higher in relation to maternal hypothyroidism (adjusted difference 20 g, 95% CI 10-30 g). Hyperthyroidism was associated with small-for-gestational-age (adjusted OR 1.15, 95% CI 1.10-1.20) and hypothyroidism with large-for-gestational-age children (adjusted OR 1.24, 95% CI 1.17-1.31). Conclusions: Based on Danish nationw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 42 publications
5
62
1
4
Order By: Relevance
“…This would fit the results of the recently published, Generation R study, which suggests that high maternal fT 4 during the first trimester is associated with low birth weight indicating a much more complex relationship (77). Moreover, Danish registry studies have shown low birth weights in children born to mothers with hyperthyroidism, and high birth weight in hypothyroidism (78). Currently, we know very little about the effects of maternal T 4 therapy on TH concentrations in the foetus and whether the additional T 4 dosage is indeed transferred through a variably disturbed utero-placental unit.…”
Section: Th Concentrations In the Offspringsupporting
confidence: 86%
“…This would fit the results of the recently published, Generation R study, which suggests that high maternal fT 4 during the first trimester is associated with low birth weight indicating a much more complex relationship (77). Moreover, Danish registry studies have shown low birth weights in children born to mothers with hyperthyroidism, and high birth weight in hypothyroidism (78). Currently, we know very little about the effects of maternal T 4 therapy on TH concentrations in the foetus and whether the additional T 4 dosage is indeed transferred through a variably disturbed utero-placental unit.…”
Section: Th Concentrations In the Offspringsupporting
confidence: 86%
“…3). Maternal thyroid dysfunction is associated with pregnancy complications including an increased risk of preterm birth and deviations in birth weight (73). Thus, it can be speculated if an increased risk of neurodevelopmental disorders in children born to mothers with thyroid dysfunction is mediated via pregnancy complications.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Maternal thyroid dysfunction may adversely complicate a pregnancy and may also 'program' the fetus to later development of disease (3,19,33,34). Newly diagnosed thyroid dysfunction during a pregnancy is rare.…”
Section: Clinical Perspectivementioning
confidence: 99%